Theoretical insights on potential-dependent oxidation behaviors and antioxidant strategies of MXenes - Yumiao Tian; Pengfei Hou; Huiwen Zhang; Yu Xie; Gang Chen; Quan Li; Fei Du; Aleksandra Vojvodic; Jianzhong Wu; Xing Meng (Nature Communications)
Abstract Significant efforts have been devoted to investigating the oxidation of MXenes in various environments. However, the underlying mechanism of MXene oxidation and its dependence on the electrode potential remain poorly understood. Here we show the oxidation behavior of MXenes under the working conditions of electrochemical processes in terms of kinetics and thermodynamics by using constant-potential ab initio simulations. The theoretical results indicate that the potential effects can be attributed to the nucleophilic attack of water molecules on metal atoms, similar to that taking place in the Oxygen Evolution Reaction. Building upon these findings, we deduced the oxidation potential of the common MXenes, and proposed antioxidant strategies for MXene. Finally, we demonstrated that MBenes, the boron analogs of MXenes, may undergo a similar nucleophilic attack in water and inferred that molecule-induced Walden inversion is widely present in material reconstructions. This work contributes to a fundamental understanding MXene stability at the atomic level, and promotes the transition in materials discovery from trial-and-error synthesis to rational design.